2013
DOI: 10.1620/tjem.229.11
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle-Based Physical Activity Intervention for One Year Improves Metabolic Syndrome in Overweight Male Employees

Abstract: Regular physical activity is associated with improvements of metabolic syndrome (MetS) risk factors. Furthermore, recent physical activity guidelines for health promotion recommend that moderate to vigorous physical activity should be performed in bouts lasting ≥ 10 min. Brisk walking is a popular and readily attainable form of moderate intensity physical activity and is suitable for the majority of individuals. However, it is unclear whether brisk walking lasting ≥ 10 min is associated with improvement in Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…The results of the present study show that waist circumference, SBP, FPG, and TG significantly decreased across categories with increasing physical activity; however, HDL-C had the opposite trend. Additionally, the age-standardized prevalence of MetS and its components including abdominal obesity, elevated TG, reduced HDL-C, elevated BP, and elevated FPG decreased across categories with increasing physical activity, which was similar to the results of previous research [7,8,9,10]. The findings of the present study also show that residents were more likely to have MetS and its components across categories with decreasing physical activity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the present study show that waist circumference, SBP, FPG, and TG significantly decreased across categories with increasing physical activity; however, HDL-C had the opposite trend. Additionally, the age-standardized prevalence of MetS and its components including abdominal obesity, elevated TG, reduced HDL-C, elevated BP, and elevated FPG decreased across categories with increasing physical activity, which was similar to the results of previous research [7,8,9,10]. The findings of the present study also show that residents were more likely to have MetS and its components across categories with decreasing physical activity.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the cross-sectional study design does not allow for quantification of the importance of physical activity in the development of MetS, which limits our ability to comment on causal relationships between physical activity categories and MetS. However, previous studies in other countries have demonstrated the importance of physical activity in the development of MetS [9,10]. Despite these limitations, the strengths of the present study include the fact that its results are based on findings in a large, representative sample of suburban dwellers in Beijing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several randomized controlled trials (RCT) have provided evidence of the benefits of physical activity on certain CVD risk factors, including reduction in systolic blood pressure (SBP) [1315], improvements in lipid profile [16, 17], and anthropometric measurements [13, 18]. However, other studies found no such benefits [1922].…”
Section: Introductionmentioning
confidence: 99%
“…Sedentary time, independent of the time spent in moderate to vigorous intensity physical activity, is associated with health risks including type 2 diabetes [3], cardiovascular disease [3,4], metabolic syndrome [5], weight gain [6,7] and obesity [8,9]. Consequently, increased attention is being paid to the development of intervention methods that focus on reducing sedentary time and increasing physical activity levels for the purpose of improving overall health [10,11]. Little is currently known about the effect of such interventions on total wellness, a concept which encompasses much more than physical health.…”
Section: Introductionmentioning
confidence: 99%